Back Cover. (29th August 2022) - Wei, Hong; Yang, Ting; Chen, Jie; Duan, Ting; Jiang, Hanyu; Song, Bin
Abstract : The cover image is based on the Review Article Prognostic implications of CT/MRI LI‐RADS in hepatocellular carcinoma: State of the art and future directions by Hong Wei et al., https://doi.org/10.1111/liv.15362 .